- Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan dan Perhitungan Biaya Produksi Detergent Cair Ramah Lingkungan pada Usaha Mikro dan Kecil di Kelurahan Meruya Utara - Nurlis, Nurlis; Chairunesia, Wieta (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Liquid detergent, in addition to being useful as a cleaning agent, also has negative impacts on user health and the environment. Therefore, it is crucial to empower Micro and Small Business actors by providing assistance and training on the harmful effects of chemical ingredients used in the production of liquid detergent, the use and formulation of environmentally friendly detergent, accurate cost calculation, and practical training in producing liquid detergent using simple production machines. Participants are taught how to calculate the total cost of raw materials per unit of liquid detergent, take into account packaging and labor costs, and then determine a reasonable profit margin. This process ensures that participants are not only capable of making the product but also understand the business aspects, thus preparing them to market the environmentally friendly liquid detergent. The entire training program ran smoothly without significant obstacles; the availability of materials and tools had been well-prepared, and collaboration between the implementation team and local partners was excellent. Keywords: Simple Technology Production Machine; Environmentally friendly liquid detergent; Production cost